A feasibility study of variable linkage mechanisms for adjustable table fans with selective rotation angles - Lee, Soo-Han; Han, Jeong-Eun; Kim, Do-Hun; Kim, Sang-Hyun (International Journal of Engineering and Technology, 2019)
This paper addresses a relatively simple method that enables to adjust the rotation angle of the output linkage to fit desired situations using variable four-bar linkage mechanism. The selective rotational angle sections are determined by experiments and the appropriate lengths of linkage to fit each section are analytically calculated. Changes in the linkage length are implemented by the rotational motion using a grooved cylindrical cam. The presented variable linkage mechanism is applied to the commercial table fans, which is a representative product using a four-bar linkage system, to enhance its efficiency through the adjustment of rotation angles. Finally, the feasibility of the proposed variable linkage mechanism is verified through fabrication and measurement.